PERSEPSI MAHASISWA KEPERAWATAN TERHADAP PEMBELAJARAN ONLINE Indonesian Nursing Students’ Perception of Online Learning : A Descriptive Study - Citra Setyo Dwi Andhini (Masker Medika, 2023)
Introduction: Online learning is a novel approach that requires adaption and development. The process of adapting and transitioning to online learning methods impact various aspects of learning components, especially among students. Negative perceptions of e-learning have been expressed by student, potentially leading to psychological pressure due to encountered challenges. This study aims to describe nursing students' perceptions of online learning Method: A cross-sectional approach was employed among nursing students in Indonesia. Data was collected online through a Google Form across three regions in Indonesia: Java and Sumatra, Bali and Nusa Tenggara Timur (NTT), and Maluku. Thirteen questions were used to measure respondents' perspectives using a Likert scale. A total of 403 nursing students participated in the study, including Diploma, Bachelor's, and Professional Nursing Program students. Results: 46% of respondents were unsure about the benefits of online learning. 84% agreed that poor internet connectivity and scheduling difficulties (55%) were barriers. 57% of respondents believed that online learning is suitable for theoretical aspects, but strongly disagreed with using it for practical/clinical components (52%). Respondents agreed that instructors provide timely responses (52%) and feedback (75%). 37% of respondents agreed that online learning could incorporate conventional/classroom teaching methods. 36% lacked confidence in performing patient procedures after online learning and expressed uncertainty about taking exams (45%). 57% of respondents preferred a mixed teaching approach (classroom, clinical, and online) Respondents consider online learning more appropriate for theoretical instruction, leading to uncertainty in applying practical skills after online learning. Discussion: Respondents consider online learning more appropriate for theoretical instruction, leading to uncertainty in applying practical skills after online learning.